MSME transformation through modern entrepreneurship strategies: An asset-based community development approach - Asbara, Nurkhalik Wahdanial; Rizal, Faisal; Mubyl, Mutiarini; Hernawan, Hernawan; Mujaddid, Mujaddid; Fahrullah, Muh. (Community Empowerment, 2025)
MSMEs in Cenrana Village face significant challenges in the modern market due to low product quality standards, weak brand identity, and a lack of business legality. This community service program aims to strengthen local competitiveness through the Asset-Based Community Development (ABCD) approach. The implementation stages involved identifying local assets, product innovation workshops, branding and digital marketing training, and assistance in obtaining Business Identification Numbers (NIB). The results demonstrated a significant increase in the managerial capacity and confidence of the entrepreneurs. Participants successfully optimized raw material selection and more efficient production techniques, created more attractive visual brand identities, and gained a better understanding of online marketing mechanisms. Furthermore, the program facilitated business legality through the issuance of NIBs, providing a foundation for capital access and market expansion. The integration of product innovation and legal compliance has proven effective in transforming rural MSMEs into more professional and competitive business entities.